STUDI ETNOBOTANI TANAMAN OBAT BERBASIS PENGETAHUAN LOKAL MASYARAKAT DI KARO, MEDAN, DAN SIMALUNGUN - Handayani, Dina; Sanimah, Sanimah; Haniyyah, Ummu; Sitompul, Aida Fitriani; Gultom, Rahmad H.; Pratiwi, Nanda (Yayasan Nusantara Hasana Berdikari, 2025)
This study aims to describe local plant species used as traditional medicine by communities in North Sumatra. The research method employed in-depth interviews with communities in three locations including Karo, Medan and Simalungun. The research results identified 81 species of local medicinal plants from 39 botanical families, with the Zingiberaceae family dominating (13 species, 16.05%), followed by Asteraceae (7 species, 8.64%), Piperaceae and Fabaceae (5 species each, 6.17%). Ginger (Zingiber officinale) was the most commonly used plant across three different locations. The most utilized plant parts were leaves (48.15%), rhizomes (22.22%), and fruits (13.58%). The primary processing methods were boiling (40.7%) and pounding (22.2%). This study demonstrates that North Sumatran communities possess diverse traditional knowledge in utilizing local medicinal plants that needs to be documented and preserved.